O Programa de Reestruturação e Expansão das Universidades Federais e o seu reflexo na política de extensão da Universidade Federal do Maranhão: o caso do Campus Pinheiro - Silva, Chrystiane Campelo da (2017)
This dissertation, through the in-depth evaluation methodology, has the objective of analyzing the Support Program for Restructuring and Expansion Plans of the Federal Universities (REUNI) at the Federal University of Maranhão at Campus Pinheiro. The program, which began in 2007 and ends in the year 2012, becomes a topic that is much discussed and evaluated by many researchers, because its general objective of increasing enrollments has promoted academic and structural changes. In order to deepen these changes, the bibliography chosen, the institutional documents and questionnaires based and promoted results beyond what was expected. To complement the research, was also made historical, social and economic survey of the city of Pinheiro. The study showed that it is through the adhesion to REUNI that the Pinheiro Campus resumes academic activities through the provision of regular courses, as well as, it promotes an exchange of cultures due to the number of servers and students coming from other regions. These students now reside in the municipality of Pinheiro, following their approval in public competition or in the case of students, by the National High School Examination. This characteristic of pluriculturalism favors coordinated social and educational actions based on Extension Projects to address local handicaps. The research sought to understand how extension projects are being planned and executed. Finally, it is possible to identify differences in the extensionist proposals developed before REUNI and after REUNI.